The use of technology by older people - Azuddin, Muna; Abd Malik, Sofianiza (2012)
There are benefits and issues of technology used by people in different aspect of life. This paper examines some literatures on the matters faced by older people in accepting technology in their life. Since most of older people did not rise together with the development of technology, it is important to find their acceptance level of technology adoption. This paper also discusses research conducted in evaluating technology used by older people; and appropriate actions that need to be taken in order to promote the use of technology among them.